Social Capital and Environmental Ethics of Farmers - Richie Rianti (International Journal of Ethics and Society, 2021)
Background: Benefiting from environmental ethics is a prerequisite for solving environmental problems. On the other hand, it seems unlikely to solve these problems without considering the social capital of society, so this study was conducted to identify environmental ethics and the impact of social capital on it. Method: It is an applied correlation research. The statistical population of this study was all farmer, 178 of whom were selected as a statistical sample based on Bartlett table and random sampling method. A researcher made questionnaire was used to collect information. Data were analyzed by Pearson and Spearman correlation and multi-regression analysis. Results: The results indicate that social capital and all its components are correlated with environmental ethics at the level of 0.001%. Conclusion: The results indicate that the promotion of social capital among farmers can improve environmental ethics and therefore in the end, some suggestions have been made based on this.